Strong metal-support interaction boosts activity, selectivity, and stability in electrosynthesis of H₂O₂ - Zhang, Junming (2022)
Noble metals have an irreplaceable role in catalyzing electrochemical reactions. However, large overpotential and poor long-term stability still prohibit their usage in many reactions (e.g., oxygen evolution/reduction). With regard to the low natural abundance, the improvement of their overall electrocatalytic performance (activity, selectivity, and stability) was urgently necessary. Herein, strong metal-support interaction (SMSI) was modulated through an unprecedented time-dependent mechanical milling method on Pd-loaded oxygenated TiC electrocatalysts. The encapsulation of Pd surfaces with reduced TiO2-x overlayers is precisely controlled by the mechanical milling time. This encapsulation induced a valence band restructuring and lowered the d-band center of surface Pd atoms. For hydrogen peroxide electrosynthesis through the two-electron oxygen reduction reaction (ORR), these electronic and geometric modifications resulted in optimal adsorption energies of reaction intermediates. Thus, SMSI phenomena not only enhanced electrocatalytic activity and selectivity but also created an encapsulating oxide overlayer that protected the Pd species, increasing its long-term stability. This SMSI induced by mechanical milling was also extended to other noble metal systems, showing great promise for the large-scale production of highly stable and tunable electrocatalysts.